Penguatan Penguasaan Kitab Kuning Melalui Program Unggulan Turats di MA Sunan Ampel Pare - Riyadlul Badi'ah; Marita Marita Lailia Rahman (Universitas Islam Tribakti Lirboyo Kediri, 2023)
This article aims to discuss the reinforcement provided by MA Sunan Ampel Pare so that students are able to understand the yellow book through the Turats program, because it is under the auspices of the Islamic boarding school. Through qualitative research with a case study approach, research results were obtained, namely: based on BF Skinner's theory, a person's behavior is controlled by operant conditioning (role conditioning). The Operant-conditioning procedures carried out by MA Sunan Ampel so that students master the book are: 1) reinforcement schedule: providing nahwu-sharaf material and exercises (positive) as well as giving low grades and punishments (negative); 2) formation: carried out through habituation and stages, namely class x still understanding the nahwu-sharaf material and class xii then the book directly; 3) behavior modification: change the behavior of being lazy about doing exercises with personal advice; 4) generalization and discrimination: obliging to attend the Islamic boarding school.